2004
DOI: 10.1016/s0002-9440(10)63324-x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Gene Expression in Nonneoplastic and Malignant Brain

Abstract: Malignant gliomas are uniformly lethal tumors whose morbidity is mediated in large part by the angiogenic response of the brain to the invading tumor. This profound angiogenic response leads to aggressive tumor invasion and destruction of surrounding brain tissue as well as blood-brain barrier breakdown and life-threatening cerebral edema. To investigate the molecular mechanisms governing the proliferation of abnormal microvasculature in malignant brain tumor patients, we have undertaken a cell-specific transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
140
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(158 citation statements)
references
References 27 publications
(26 reference statements)
15
140
0
3
Order By: Relevance
“…However, the molecular mechanisms that control endosialin expression have remained elusive (Rettig et al, 1992;Brady et al, 2004;Davies et al, 2004;Madden et al, 2004;Dolznig et al, 2005;MacFadyen et al, 2005;Huber et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular mechanisms that control endosialin expression have remained elusive (Rettig et al, 1992;Brady et al, 2004;Davies et al, 2004;Madden et al, 2004;Dolznig et al, 2005;MacFadyen et al, 2005;Huber et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have confirmed that endosialin is upregulated in blood vessels and activated stromal fibroblasts in human colorectal, brain and breast tumours as well as in mouse xenograft models (Carson-Walter et al, 2001;Brady et al, 2004;Davies et al, 2004;Madden et al, 2004;Dolznig et al, 2005;MacFadyen et al, 2005MacFadyen et al, , 2007Huber et al, 2006;Rupp et al, 2006). Endosialin expression is restricted to capillaries and shows a heterogeneous pattern typical for molecules involved in vascular reorganisation.…”
mentioning
confidence: 92%
“…Recently, a new SDF-1 receptor named CXCR7 has been discovered [66,67]. CXCR7 is also expressed on tumor cells and endothelium and regulates tumor growth [67,68]. As such, it is conceivable that CXCR4-independent effects of SDF-1 on angiogenesis could potentially be attributed to CXCR7 [69].…”
Section: Multiples Roles Of Sdf-1 In Governing Neo-angiogenesis In Vivomentioning
confidence: 99%
“…Dwyer et al demonstrated that IL-8 has the ability to function as an angiogenic factor in glioblastoma (Dwyer et al, 2012). CXCR7 is reported to be upregulated in blood vessels of malignant brain tumors and mediates the recruitment of endothelial cells to the SDF-1 secreted tumor cells (Madden et al, 2004).…”
Section: Expression Of Chemokines and Chemokine Receptors In Brain Tumentioning
confidence: 99%